« Si vous votez la loi d’exclusion aujourd’hui, c’est vous qui serez exclus demain » - Bilel Kchouk (L’Année du Maghreb)
This research focuses on the effect of the fall of Ben Ali’s regime (2011) on the role and trajectory of the Tunisian political elites. Our aim is to analyze the impact of the institutional change and the strategies underlying the repositioning of the Tunisian elites in the light of the Eastern Europe situations. As in the case of the fall of communism, we defend the idea of an enlargement of the political elite space allowing newcomers to cohabit with former political elites. This repositioning took place through multiple logics such as political sacrifice of several agents, networking solidarity and bargaining. It is, above all, a proof of a great circulation and a mild political reproduction. The cohabitation between the Ben Ali’s elite and the emerging elite makes it possible to emphasize the ambiguity of the restructuring and the overlaps between the «old» and the «new» regime.